Influence of ultrafine-grained structure of Ti-42Nb-7Zr alloy on energy dissipation and storage under quasi-static tension; Materials Letters; Vol. 375 - Legostaeva E. V. Elena Viktorovna; Eroshenko A. Yu. Anna Yurjevna; Vavilov V. P. Vladimir Platonovich; Skripnyak V. A. Vladimir Albertovich; Uvarkin P. V. Pavel Viktorovich; Tolmachev A. I. Aleksey Ivanovich; Bataev V. A. Vladimir Anatoljevich; Chulkov A. O. Arseniy Olegovich; Kozulin A. A.; Skripnyak V. V. Vladimir Vladimirovich; Sharkeev Yu. P. Yury Petrovich (2024, 2024)
Title screen